Reducing the rate of the Shunt infection by washing with specific antibiotics before planting - محمد صالح علي (Latakia University Journal -Medical Sciences Series, 2023)
Background: Shunt infection in hydrocephalus patients is a severe, even life-threatening complication. Antibiotic-impregnated shunts have been developed in an attempt to reduce rate of shunt infection. The study was performed to analyze if AIS can diminish the rate of shunt infection. The pathogenic nature of shunt infection in patients with AIS systems and those without antibiotic impregnated shunts (non-AIS) was compared. Methods: Over a period from 2017 to 2022 in the Department of Neurosurgery at University Hospital of Tishreen, shunt surgery was performed in 258 patients. In 86 patients AIS systems were implanted. Shunt catheters were commercially impregnated with Vancomycin. Analysis of the clinical data included sex, age, classification of hydrocephalus, shunt types and risk factors for shunt infection [age (< 1 year and > 80 years), prematurely born patients, external ventricular drainage, former shunt infection, former systemic infection, disturbance of consciousness.. Infection rates and underlying bacterial pathogens of patients with AIS were compared to patients with implanted non-AIS systems (172 patients). Results: AIS and non-AIS patients did not differ in sex, etiology of hydrocephalus and the shunt type. In the AIS group 72 out of 86 patients had at least one risk factor (83.7 %), compared to 126 patients in the non-AIS group (73.3 %). There was no significant difference between the two groups (p = 0.0629; Fisher’s exact test). In patients with no risk factors, only one patient with non-AIS suffered from shunt infection. In patients with one or more risk factors the rate for shunt infection was 7.14 % in patients with non-AIS and 6.94 % in patients with AIS. Former shunt infection (p =0.0124) was related to higher risk for shunt infection. The use of AIS had therefore no significant advantage (p = 0.8611; multiple logistic regression). Significantly related to a shunt infection was the number of shunt surgeries. 190 interventions in the AIS group (2.21 interventions per patient) and 408 in the non-AIS group (2.37 interventions per patient) had been performed (p = 0.3063; Wilcoxon). There was no shunt infection in the group of patients on whom only one shunt surgery was performed. In patients with at least two shunt surgeries the infection rate was 9%. The infection rate in AIS patients was 5/52 (9.6 %) and in the non-AIS 10/114 (8.77 %), (p = 1.0). Staphylococcus epidermidis was the most frequent pathogen for shunt infection. Fourteen out of 15 infections occurred within the first 6 months of surgery. The most frequent pathogen for shunt infection was S. epidermidis. No toxic or allergic complications were seen using the AIS shunt systems. The presented data show a remarkably low infection rate of 5.8 % in the non-AIS group compared to other studies which demonstrated a significant decrease in the infection rate by AIS. Conclusion: AIS did not significantly reduce shunt infection in hydrocephalus patients in the presented study. In the AIS group three patients suffered from shunt infections caused by skin ulceration or neurosurgical procedures with exposure of the cerebrospinal liquor after shunt implantation. AIS was not developed to prevent infection in such cases, therefore an advantage of AIS can not be excluded. In view of the presented data and the small number of reported studies a prospective randomized multicenter study is required.